1970
DOI: 10.2105/ajph.60.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and satisfactions of low-income families receiving comprehensive pediatric care.

Abstract: In an experiment evaluating comprehensive pediatric care provided for low-income families, changes in attitudes and satisfactions were examined. Certain general attitudes remained unchanged, but where care was actually delivered there was increased satisfaction and an increased preference for a primary physician. The authors point up the need for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…21,37,45,57,58 In 7 of the studies, including 6 of the 7 clinical trials, patients were assigned either to a clinic designed to deliver clinician continuity or to a clinic with no physician continuity. [22][23][24][25][26]29,40,70 Unfortunately, the quality of evidence in these studies is compromised, because in only 1 study was continuity actually measured in either study group. 33 Supplemental Table 3 (http://www.annfammed.org/ cgi/content/full/3/2/159/DC1) summarizes the 20 studies examining the association between interpersonal continuity and the cost of health care.…”
Section: Resultsmentioning
confidence: 99%
“…21,37,45,57,58 In 7 of the studies, including 6 of the 7 clinical trials, patients were assigned either to a clinic designed to deliver clinician continuity or to a clinic with no physician continuity. [22][23][24][25][26]29,40,70 Unfortunately, the quality of evidence in these studies is compromised, because in only 1 study was continuity actually measured in either study group. 33 Supplemental Table 3 (http://www.annfammed.org/ cgi/content/full/3/2/159/DC1) summarizes the 20 studies examining the association between interpersonal continuity and the cost of health care.…”
Section: Resultsmentioning
confidence: 99%
“…All 4 found aspects of improved patient satisfaction in study groups with higher continuity of care. In the 1960s, Alpert and colleagues 47,57 randomly assigned 931 low-income children to receive care in a comprehensive pediatric clinic or in a traditional pediatric walk-in clinic in Boston. The care of these 2 groups was compared at 2 and 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…48,49,58 Although the intervention groups were assigned to receive care in clinics that were designed to deliver care in an interpersonal continuity model, there is no evidence in these reports that the continuity was in fact better in these clinics. In the remaining 2 trials by Alpert et al 47,57 and Wasson et al, 50 interpersonal continuity was measured by the percentage of patients who could name their physicians. Wasson et al also reported the usual provider continuity index (UPC) and the sequential continuity index (SECON) to show higher continuity scores in the intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Starfield 27 stated that longitudinality is an essential element of good primary care, and Hjortdahl and Laerum 28 described continuity as a cornerstone of the relationship. The benefits of continuity have been described: enhanced satisfaction for parents of children with chronic illnesses 29 ; improved understanding of the need for and results of a consultation 30 ; improved appointment compliance with longitudinal care 31,32 ; improved medication compliance 31,33,34 ; and reduced hospitalization rates, episodes of illness, and number of laboratory tests performed. 35 Mothers have been found to be more likely to disclose behavioral problems 31,34 ; previously addressed problems are more likely to be addressed again 17 ; and visit satisfaction is greater with the same provider.…”
Section: Discussionmentioning
confidence: 99%